Distinct Interactions with Cellular E-Cadherin of the Two Virulent Metalloproteinases Encoded by a Bacteroides fragilis Pathogenicity Island - Remacle, Albert G. (PLoS One, 2014)
Bacteroides fragilis causes the majority of Gram-negative anaerobic infections in the humans. The presence of a short, 6-kb, pathogenicity island in the genome is linked to enterotoxigenic B. fragilis (ETBF). The role of the enterotoxin in B. fragilis virulence, however, remains to be determined, as the majority of clinical isolates lack ETBF genes and healthy individuals carry enterotoxin-positive B. fragilis. The island encodes secretory metalloproteinase II (MPII) and one of three homologous enterotoxigenic fragilysin isoenzymes (FRA; also termed B. fragilis toxin or BFT). The secretory metalloproteinases expressed from the genes on the B. fragilis pathogenicity island may have pathological importance within the gut, not linked to diarrhea. MPII and FRA are counter-transcribed in the bacterial genome, implying that regardless of their structural similarity and overlapping cleavage preferences these proteases perform distinct and highly specialized functions in the course of B. fragilis infection. The earlier data by us and others have demonstrated that FRA cleaves cellular E-cadherin, an important adherens junction protein, and weakens cell-to-cell contacts. Using E-cadherin-positive and E-cadherin–deficient cancer cells, and the immunostaining, direct cell binding and pull-down approaches, we, however, demonstrated that MPII via its catalytic domain efficiently binds, rather than cleaves, E-cadherin. According to our results, E-cadherin is an adherens junction cellular receptor, rather than a proteolytic target, of the B. fragilis secretory MPII enzyme. As a result of the combined FRA and MPII proteolysis, cell-to-cell contacts and adherens junctions are likely to weaken further.